Effect of AC-WC Asphalt Mixture Variations on Marshall Stability in Palangka Raya City - Purnomo, Raja Raid Nabil Putra; Fatmawati, Leily; Thompson, Michael J. (Journal of Engineering and Technological Science, 2026)
Asphalt Concrete–Wearing Course (AC-WC) is a critical pavement layer directly exposed to traffic loads and environmental conditions. In tropical cities such as Palangka Raya, variations in asphalt mixture composition significantly influence pavement durability, particularly Marshall stability. This study aims to comprehensively evaluate the effect of AC-WC asphalt mixture variations on Marshall stability in Palangka Raya City through a systematic synthesis of experimental studies published between 2012 and 2025. The research method employed a qualitative–quantitative comparative analysis of 30 peer-reviewed journal articles, theses, and dissertations focusing on AC-WC mixtures incorporating modifiers such as Asbuton, polymer additives, fillers, temperature variations, and immersion conditions. The results indicate that asphalt modifiers—especially polyethylene-based polymers, Asbuton granular asphalt, and alternative fillers—consistently enhance Marshall stability, with optimal stability generally achieved within 2–5% additive content. Environmental factors, including water immersion and temperature variations, were found to significantly reduce stability if not properly controlled. Overall, most AC-WC mixtures evaluated met the Indonesian Bina Marga 2018 specifications, demonstrating their suitability for heavy traffic conditions. This study contributes to pavement engineering by providing a consolidated technical reference for optimizing AC-WC mixture design in tropical urban environments.